Seventh International Conference on Document Analysis and Recognition, 2003. Proceedings.
DOI: 10.1109/icdar.2003.1227718
|View full text |Cite
|
Sign up to set email alerts
|

Generation of hierarchical dictionary for stroke-order free Kanji handwriting recognition based on substroke HMM

Abstract: This paper describes a method of generating a Kanji hierarchical structured dictionary for stroke-number and stroke-order free handwriting recognition based on substroke HMM. In stroke-based methods, a large number of stroke-order variations can be easily expressed by just adding different stroke sequences to the dictionary and it is not necessary to train new reference patterns. The hierarchical structured dictionary has an advantage that thousands of stroke-order variations of Kanji characters can be produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Moreover, a new way of writing a character, differing only in stroke order, can easily be supported by simply adding the corresponding stroke sequence in the dictionary [Nakai et al 2001], thereby circumventing the need for more samples and fresh training. The sharing of stroke labels across character classes also allows the design of stroke-based recognition strategies [Nakai et al 2001[Nakai et al , 2003Yamasaki 1999], and enables the realization of certain incremental handwriting-based text entry methods (e.g., QuickStroke [Matic et al 2002]). …”
Section: Advantages and Pitfalls Of Stroke-level Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a new way of writing a character, differing only in stroke order, can easily be supported by simply adding the corresponding stroke sequence in the dictionary [Nakai et al 2001], thereby circumventing the need for more samples and fresh training. The sharing of stroke labels across character classes also allows the design of stroke-based recognition strategies [Nakai et al 2001[Nakai et al , 2003Yamasaki 1999], and enables the realization of certain incremental handwriting-based text entry methods (e.g., QuickStroke [Matic et al 2002]). …”
Section: Advantages and Pitfalls Of Stroke-level Modelingmentioning
confidence: 99%
“…Nakai et al [2001] identified 25 substrokes in Kanji characters based on their direction and length, which may be used to express any Kanji character. While a hierarchical dictionary consisting of substrokes, strokes, radicals and characters is manually built for recognition of Kanji characters featuring known stroke orders, new stroke orders are learnt by generating permutations of the known stroke orders in the dictionary and matching with the samples in the training data [Nakai et al 2003]. Yamasaki [1999] proposes a two-stage stroke clustering approach for Japanese character recognition.…”
Section: Stroke-level Modelingmentioning
confidence: 99%
“…HMMs were first described in a series of statistical papers [51] and applied to speech recognition [52][53] in the middle of the 1970s. Then, they were applied widely to online handwriting [12][13][14][15][16][17][18][19][20][21] and offline word recognition [32][33][34][35][36][37][38].…”
Section: Site: Feature Points From An Input Pattern S={s1 S2 S3…s12}mentioning
confidence: 99%
“…For online recognition, structural features are often employed with hidden Markov models (HMMs) [12][13][14][15][16][17][18][19][20][21] or Markov random field (MRF) [29,30]. However, since the un-structural features are easily extracted from an online handwritten pattern by discarding temporal and structural information, we can apply the un-structural method as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation